The Length of Maternity Leave and Family Health - Louise Voldby Beuchert; Maria Knoth Humlum; Rune Majlund Vejlin (Institute for the Study of Labor (IZA), 2014)
We study the relationship between the length of maternity leave and the physical and psychological health of the family. Using a reform of the parental leave scheme in Denmark that increased the number of weeks of leave with full benefit compensation, we estimate the effect of the length of maternity leave on a range of health indicators including the number of hospital admissions for both mother and child and the probability of the mother receiving antidepressants. The reform led to an increase in average post-birth maternity leave of 32 days. We find limited evidence that the increase in the length of maternity leave matters for child or maternal health outcomes and thus we complement the existing evidence on maternity leave expansions that tends to find limited effects on children's later developmental, educational, and labor market outcomes. Our results suggest that any beneficial effects of increasing the length of maternity leave are greater for low-resource families.
Keywords: I18; J13; J18; 330; maternity leave; family health; regression-discontinuity